2014
DOI: 10.1902/jop.2014.130291
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility of Periodontal Streptococcus constellatus and Streptococcus intermedius Clinical Isolates

Abstract: Subgingival S. constellatus and S. intermedius exhibited variable antibiotic susceptibility profiles, potentially complicating empirical selection of periodontitis antibiotic therapy in patients who are species positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 32 publications
2
27
0
2
Order By: Relevance
“…Moreover, nearly all subgingival isolates of yellow complex species (streptococci) were susceptible to sitafloxacin, although Streptococcus strains resistant to levofloxacin, azithromycin or clindamycin were identified during the course of the periodontal treatment. These findings are in line with the recent report by Rams et al [24], which showed the variable antibiotic susceptibility profiles of some of the subgingival streptococci.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, nearly all subgingival isolates of yellow complex species (streptococci) were susceptible to sitafloxacin, although Streptococcus strains resistant to levofloxacin, azithromycin or clindamycin were identified during the course of the periodontal treatment. These findings are in line with the recent report by Rams et al [24], which showed the variable antibiotic susceptibility profiles of some of the subgingival streptococci.…”
Section: Discussionsupporting
confidence: 93%
“…An earlier study reported that S. intermedius levels were higher in supragingival but not in subgingival plaque of T2DM patients when compared to controls (Hintao, Teanpaisan, Chongsuvivatwong, Ratarasan, & Dahlen, ). SAG seems to be resistant to periodontal therapy, as their levels remain high in periodontal sites after periodontal treatment (Feres et al., ) and are resistant to multiple antimicrobials (Rams, Feik, Mortensen, Degener, & van Winkelholf, ). In addition, these organisms are involved in invasive infections, demonstrated by their ability to cause abscesses (Asam & Spellerberg, ).…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate glycaemic control was associated with increasing levels of succinate/acetate producers and decreased levels of butyrate producers, which may interfere with the immune response against subgingival microbiota. The altered microbial profile may also influence periodontal treatment outcomes by selecting species resistant to mechanical treatment and even to antibiotics commonly used in the periodontal therapy, such as the anginosus group of streptococci (Feres et al., ; Rams et al., ). Furthermore, our data suggest that shifts in microbiome signatures in T2DM patients with inadequate glycaemic control may play a role locally in periodontal tissues and increase the risk of infection diseases commonly associated with diabetes, by selection of pathobionts such as S. agalactiae .…”
Section: Discussionmentioning
confidence: 99%
“…constellatus oral cavity, gastrointestinal tract [42,43] potential role in chronic periodontitis [44] NDA Note: NDA -no data available production of mycotoxins. Special attention should be paid to filamentous fungi that belong to primary colonizers -fungi able to grow in the lowest water activity environment, i.e., Penicillum expansum [45][46][47].…”
Section: Bacterial Species Possible Sources Pathogenicity Biodeteriormentioning
confidence: 99%